Punished but not prepared: An exploration of novice writers’ experiences of plagiarism at university - Crook, Stephanie; Cranston, Jerome (Canadian Perspectives on Academic Integrity, 2021)
This paper reports on the results of a study of first- and second-year Canadian undergraduate students’ perceptions of academic integrity and plagiarism. Using a sequential explanatory research design, the first phase involved a Likert-type survey that gauged students’ perceptions (n = 350) of academic integrity and plagiarism, whereas in phase two, students (n = 3) were interviewed to further explore their perceptions. The findings indicate that students often categorize acts as either plagiaristic or non-plagiaristic despite their inability to clearly explain how they made their determinations. Furthermore, the participants in the study experienced the university as being predisposed to punitive action rather than to supportive action. These experiences are significant because the students were only beginning to understand the nuances of academic integrity. Overall, the findings indicate that novice university writers would benefit from formative pedagogical processes to guide them to producing effective academic writing in a university context. Responding with punitive measures to ambiguous situations appears to slow down the internalization of academic integrity principles.